الجباية العادية كآلية لتمويل الخزينة العمومية في ظل جائحة كورونا دراسة تحليلية للسنوات (2019-2022) - نوري, يوسف; بضياف, صالح (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة إلى تسليط الضوء حول أثر الجباية العادية على تمويل الخزينة العمومية في ظل جائحة كورونا وهذا بتسليط الضوء حول الجباية العادية كمتغير مستقل وأثرها على تمويل الخزينة العمومية بإعتبارها متغير تابع، كما إعتمدنا على المنهج الوصفي والتحليلي للإجابة عن الإشكالية المطروحة ،وقد حددت مدة الدراسة بأربعة سنوات بداية من ظهور الجائحة2019 الى غاية 2022، وخلصت هذه الدراسة إلى أن الجباية العادية تعتبر مصدر من مصادر تمويل الخزينة العمومية ،وقد توصلت هذه الدراسة أيضا إلى أن الإيرادات الجبائية لم تغطي النفقات العامة لدولة وهذا من خلال العجز الملحوظ طيلة الفترة المدروسة، وأوصت الدراسة إلى تفعيل رقمنة وعصرنة الإدارة الجبائية، من أجل زيادة وتحسين المردود الجبائي ،خاصة في ظل القيود التي فرضتها جائحة كوروناـ The ordinary collection as a mechanism for financing the public treasury in light of the Corona pandemic This study aimed to shed light on the impact of regular collection on the financing of the public treasury in light of the Corona pandemic, and this is by shedding light on the regular collection as an independent variable and its impact on the financing of the public treasury as a dependent variable. The study is four years old, starting from the emergence of the pandemic 2019 until 2022, and this study concluded that the regular collection is a source of financing the public treasury, and this study also found that the fiscal revenue did not cover the public expenditures of the state and this is through the noticeable deficit throughout the studied period, and recommended The study aims to activate the digitization and modernization of the fiscal administration, in order to increase and improve the fiscal return, especially in light of the restrictions imposed by the Coronal pandemic for the years (2019-2022).
The ordinary collection as a mechanism for financing the public treasury in light of the Corona pandemic Analytical study for the years (2019-2022
مقال
Keywords: جباية العادية ، خزينة العمومية، جائحة كورونا